Morphological, molecular, and histopathological studies on Hadjelia truncata from Columba livia domestica and its role as an environmental biological indicator - Albeshr Mohammed; Alsharief Rajwa; Al-Otibi Fatimah; Al-Shaebi Esam M.; Mohammed Osama B.; Abdel-Gaber Rewaida (Journal of Nematology, 2023)
Pigeons are a cosmopolitan group of birds with abundant and large populations associated with human activities. This study focused on determining parasitic infections within domestic pigeons (Columba livia domestica). Forty-eight pigeons were examined for infections, of which 29.16% were infected with a nematode parasite, identified as Hadjelia truncata (Habronematidae), under the koilin layer of their gizzards. The population of nematodes in infected gizzards did not exceed 20 adult worms. DNA from the gizzard worms was extracted and subjected to PCR using primers that amplify the partial 18S rDNA and cytochrome C oxidase subunit I (COX I) regions. Identification of this parasite based on microscopic study revealed the presence of trilobed lips with cephalic papillae and amphidial pores, as well as other characteristic features. In males, spicules were unequal with the presence of six pedunculated pairs of caudal papillae (4 pre- and 2 post-anal) and a tail surrounded with caudal ala. In females, the vulva was a rounded aperture located in front of the posterior end of the esophagus and uteri, which was filled with numerous embryonated eggs. DNA Sequences from partial 18S rDNA were homologous to sequences obtained from H. truncata in GenBank with a high percentage of identity. DNA sequences from mitochondrial gene COX I, however, were unique, and they were the first sequenced for H. truncata, since no sequences for this taxon were previously available in GenBank. Histopathological examination revealed enlargement of infected gizzards in comparison to non-infected ones, with the presence of necrosis and interstitial infiltration in the koilin layer. Concentrations of heavy metals (Fe, Cu, Zn, Cd, Cr, and Co) were measured using inductivity-coupled plasma in tissues (liver, muscles, and gizzards) from infected and non-infected pigeons as well as their parasites. Results showed different affinities of metals to tissues. Recovered parasites can minimize element concentration from their pigeon tissues. In Saudi Arabia, this study was considered the first report identifying pigeon nematodes and evaluating of the effects of their pathogenicity on the animals’ welfare, as well as their application as a useful tool for monitoring environmental pollution.